Effect of replacement of barley grain with wheat bran on testicular parameters, semen characteristics, and body weight gain and economics of mating Doyogena ram - Tamirat, Petros (Wachemo University, 2024)
To assess the impact of replacing barley with wheat bran, this study explores the effects on testicular parameters, semen characteristics, and body weight gain in Doyogena rams. The experimental design involved four groups (T1, T2, T3, and T4) consisting of intact one-year-old rams (averaging 25.62 ± 1.91kg body weight), employing a randomized block design. The control group (T1) remained unaltered; while T2 received a concentrate mixture comprising 100% crushed barley grain. On the other hand, groups T3 and T4 had 50% and 100% substitution of barley grain with wheat bran, respectively. Additionally, noug-seed cake was introduced as a supplement to ensure normal body weight, while natural pasture served as roughage, provided ad-libitum to all rams. This on-farm study spanned a period of 90 days with additional 14-days for acclimatization. The semen samples were collected at the beginning and end study from each experimental ram using an artificial vagina. Fresh semen analysis revealed significant difference in semen volume, sperm concentration, and sperm motility in supplemented groups (T2, T3, and T4) compared to the group (T1). Similarly, an increased in body weight, scrotal circumference, and testicular diameter were observed (P<0.05) in the supplemented groups compared with the control group. Unlike wise, within the supplemented groups, no significant differences (P>0.05) were found in all examined variables. Notably, the body weight of rams positively correlated with scrotal circumference (r=0.714), testicular diameter (r=0.672), semen volume (r=0.733), and the concentration of spermatozoa (r=0.753). Based on partial budget analysis, T4 outperformed other groups, ensuring the highest profit. Replacing barley with wheat bran in the diet of Doyogena rams has been found to enhance both their reproductive performance and body weight gain. The supplemented groups (T2, T3, and T4) demonstrated superior semen quality, increased body weight and larger scrotal circumference, compared to the control group (T1). Additionally, T4 emerged as the most economically viable option for increasing testicular parameters, weight gain and semen quality, in Doyogena rams.